Componimenti musicali (1739): for Harpsichord - Muffat, Gottlieb 1690-1770; Hogwood, Christopher 1941-2014 (Bologna Ut Orpheus, 2009)
With no affectation or false modesty, Gottlieb Muffat described the 1739 publication of his Componimenti musicali per il cembalo as 'the most beautiful product to be met with in all Germany'. It was patently one of the most lavish and cosmopolitan productions of all 18th-century music printing; with paper of large format and high quality, an extravagant title-page, meticulous and calligraphic engraving, prefaces in several languages and a dedication to the Holy Roman Emperor, Muffat aimed to set it apart from other volumes of keyboard music of this period such as Couperin's Pièces de Clavecin or Bach's Klavierübung, and also from his earlier collection of versetts and toccatas aimed at the professional church musician (72 Versetl sammt 12 Toccaten, Vienna, 1726). The Componimenti represent a polished selection from his secular keyboard music and the publication was directed at the royal household. His title-page proudly announces that he was not only Organista di Corte e Camera (i.e. in public and private) to the Emperor, but also Maestro di Cembalo to the two arch-duchesses, Maria Theresa and her sister Maria Anna.
Keywords: 18th Century (1701-1800); Keyboard music; Harpsichord